Menstrual cycle performance barriers experienced by elite women football players and their management strategies applied: A semi-structured interview-based study - Read, P.; Rosenbloom, C.; Mehta, R.; Owen, H.; Jobson, E.; Okholm Kryger, K. (Science and Medicine in Football, 2025)
The objective of this study was to investigate the barriers experienced by elite women football players due to their menstrual cycle, and coping strategies utilised against these barriers. Fifteen elite women footballers from two English Women`s Super League clubs (age: 25.2 years [18-33]) were interviewed using semi-structured interviews, developed using piloting and peer review. Data was audio recorded, transcribed verbatim and analysed thematically using NVivo. Analysis of 27,438 words unveiled key themes: internal barriers, external barriers, coping strategies, and player needs. Fear of leakage, associated with kit colour (n = 15) and lack of effective sanitary products (n = 12), and injury anxiety (n = 7), associated with ACL injury (n = 5), were the most common barriers. To combat these issues, players use internal (feeling fortunate n = 9) and external (support from teammates n = 6; support from club staff n = 4) coping strategies. The findings indicated that menstruation presents significant barriers to players. Increased awareness of menstruation-related barriers to performance and targeted intervention are achievable through staff and player involvement and by minimising concerns of visible leakage by kit interventions.